(untitled) (Fiep Bulletin - online, 2025)
The article presents a study on the lifestyle profile of participants in the Movimentise extension project, which aims to mitigate the onset of non-communicable chronic diseases (NCDs) in the elderly, such as obesity, diabetes, and heart diseases, through physical activities and discussion circles based on the pillars of Lifestyle Medicine (LM). The target audience consists of elderly individuals from the city of Campos dos Goytacazes, which is facing a growing number of people over the age of 60, posing challenges for healthcare services. Aging is described as a natural and universal process that can be influenced by various factors, such as lifestyle, health, and socioeconomic conditions. The study highlights the importance of maintaining an active lifestyle to delay the effects of aging, improve quality of life, and prevent chronic diseases. The Movimentise project, through exercise classes and educational activities, supports the elderly in maintaining their autonomy and quality of life. The methodology used included a survey with 42 participants from the project, with an average age of 67 years. The evaluation tool was the Pentacle of Well-being questionnaire, which assessed aspects such as nutrition, physical activity, preventive behavior, relationships, and stress management. The results emphasized that an active lifestyle and healthy habits are crucial for more successful aging and for preventing chronic diseases. The project also included discussion circles and social activities, such as ecological walks, with the aim of promoting social interaction and emotional well-being among the participants.